Stacking Bagged and Boosted Forests for Classification of Noisy and High-Dimensional Data - Campos, Raphael R.; Gonçalves, Marcos André (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2018: Anais do XXXI Concurso de Teses e Dissertações, 2018)
Random Forests (RF) are one of the most successful strategies for automated classification tasks. Motivated by the RF success, recently proposed RF-based classification approaches leverage the central RF idea of aggregating a large number of low-correlated trees, which are inherently parallelizable and provide exceptional generalization capabilities. In this context, this work brings several new contributions to this line of research. First, we propose a new RF-based strategy (BERT) that applies the boosting technique in bags of extremely randomized trees. Second, we empirically demonstrate that this new strategy, as well as the recently proposed BROOF and LazyNN RF classifiers do complement each other, motivating us to stack them to produce an even more effective classifier. Up to our knowledge, this is the first strategy to effectively combine the three main ensemble strategies: stacking, bagging (the cornerstone of RFs) and boosting. Finally, we exploit the efficient and unbiased stacking strategy based on out-of-bag (OOB) samples to considerably speedup the very costly training process of the stacking procedure. Our experiments in several datasets covering two high-dimensional and noisy domains of topic and sentiment classification provide strong evidence in favor of the benefits of our RF-based solutions. We show that BERT is among the top performers in the vast majority of analyzed cases, while retaining the unique benefits of RF classifiers (explainability, parallelization and easiness of parameterization).